SIMULASI PENGARUH KECEPATAN GAS TERHADAP KARAKTERISTIK FLUIDISASI PADA FLUIDIZED BED MENGGUNAKAN METODE CFD - Asyari Daryus Daryus (Program Studi Teknik Mesin Universitas Tarumanagara, 2018)
The gas fluidization velocity or superficial gas velocity entering the fluidized bed will affect the fluidization in fluidized bed. If the superficial velocity is below the minimum fluidization velocity then there is no fluidization, and if it is more than it should be then the fluidization characteristic will be different. To obtain the effect of gas fluidization velocity to fluidization characteristics, it had been conducted the research on lab scale fluidized bed using CFD simulation method validated with the experiment data. The simulations used Gidaspow model for drag force and k-ε model for turbulent flow. From the experiments obtained that the minimum fluidization velocity was 0.4 m/s and the pressure drop was around 700 Pa. The simulation results for pressure drop across the bed were close to the experiment data for the gas fluidization velocity equal and bigger than the minimum fluidization velocity. For the velocity below the minimum fluidization velocity, there was the big differences between the simulation results and the experiment, so the simulation results cannot be used. For the fluidization velocity of 0.4 m/s and 0.45 m/s, fluidized bed showed the bubbling phenomena, and the higher velocity showed the bigger bubble. For the fluidization velocity of 0.50 m/s to 0.70 m/s, the fluidized bed showed the turbulent regime. In this regime, the bubble was breaking instead of growing and there was no clear bed surface observed. The simulation result for particle density showed that if the gas velocity was higher, the density of particles at the base of bed was decreasing since many of the particles was moving upwards. The particle density was lower in this regime than that of bubbling regime.